2018
DOI: 10.18553/jmcp.2018.24.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Medicaid Antipsychotic Medication Measures Among Children with SSI, Foster Care, and Income-Based Aid

Abstract: This project was supported by grant number U18HS020503 from the Agency for Healthcare Research and Quality (AHRQ) and Centers for Medicare & Medicaid Services (CMS). Additional support for Rutgers-based participants was provided from AHRQ grants R18 HS019937 and U19HS021112, as well as the New York State Office of Mental Health. The content of this study is solely the responsibility of the authors and does not necessarily represent the official views of AHRQ, CMS, or the New York State Office of Mental Health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
22
1
Order By: Relevance
“…Other similarities to their study are the low incidence of prior treatment with cognitive behavioral interventions and the fact that younger children were less likely to have received prior treatment. In contrast to our findings, in over half of a sample of Medicaid insured children, there was no prior psychosocial treatment in the 3 months before the antipsychotic had been prescribed [32,38]. However, our study, as well as the study by Rettew et al [7] assessed all prior lifetime treatments, which might explain this difference.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Other similarities to their study are the low incidence of prior treatment with cognitive behavioral interventions and the fact that younger children were less likely to have received prior treatment. In contrast to our findings, in over half of a sample of Medicaid insured children, there was no prior psychosocial treatment in the 3 months before the antipsychotic had been prescribed [32,38]. However, our study, as well as the study by Rettew et al [7] assessed all prior lifetime treatments, which might explain this difference.…”
Section: Discussioncontrasting
confidence: 97%
“…The second study also focused on Medicaid-insured children and evaluated recommendations that were based on a review of guidelines from the United States [ 31 ], addressing antipsychotic polypharmacy, dosing, prior treatment, metabolic screening, and monitoring. The authors found substantial shortcomings across recommendations [ 32 ]. However, they noted that not all relevant data might be reflected in the claims database that was used to obtain information on the course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, atypical antipsychotics are most commonly prescribed in pediatric patients for off label uses including depression, obsessive-compulsive disorder (OCD), Tourette Syndrome, post-traumatic stress disorder (PTSD), and attention deficit hyperactivity disorder (ADHD) (35). Atypical antipsychotic use in children peaked in the mid-2000s and was associated with a trend in initiating prescriptions at a younger age, although antipsychotic use has continued to rise in adolescents since that time (3,6).…”
Section: Introductionmentioning
confidence: 99%
“…Off-label use of antipsychotic medications in pediatric patients increased rapidly through the 2000s, leveling off in 2008. 6 Off-label use occurs more frequently in vulnerable populations, including children in foster care, 7,8 children with Medicaid, 9,10 minority children, 11 and children with intellectual disabilities. 12 Some states have implemented stringent oversight programs to reduce and monitor prescriptions for psychotropic medications in general and antipsychotic medications in particular.…”
Section: What Are Antipsychotics and What Are They Used For In Children?mentioning
confidence: 99%